Acceptability of Tortillas and Tamales Made with Nixtamalized Corn with Germinated Chia Flour - María Eunice Cota; Elsa Julieta Salazar (Biology and Life Sciences Forum)
Corn, Zea mays, is an ancestral food, culturally included in different forms in the Guatemalan diet. The most common form is in tortillas and tamales, which makes them suitable for incorporating other ingredients that increase their nutrient content. A sensory study was conducted with the aim of determining whether the appearance and texture of the tortilla and tamale remain acceptable when adding germinated chia seed flour (Salvia hispanica L). Germination was carried out for one day at 20 °C; it was prepared as flour and mixed with nixtamalized corn flour in a ratio of 10:90 and enough water to mold the tortillas; for the tamale, the same proportion of corn flour and germinated chia flour was used, and water and 8.6 percent oil were added. The tortillas and tamales were prepared and cooked in a traditional way by experts. For the acceptability test, 52 consumers were recruited, who signed the informed consent and subsequently evaluated the appearance and texture using a five-point hedonic scale (1 = I like it very much, 5 = I dislike it very much). The results indicate that the average acceptability of the appearance of the tortilla is 1.2 and the texture is 1.8. The average acceptability of the appearance of the tamale is 1.9 and the texture is 1.19. When comparing the acceptability of the appearance and texture of both preparations, a significant difference was found (p < 0.05), with the appearance and texture of the tamale being more acceptable.